„LET U MJESTU” UMETNUT U OKVIR POLITIČKIH PRI/POVIJESTI (Philological Studies, 2019)
The paper gives the analysis of Goran Stefanovski's play Flying in place, and its relation to the socio-politic context of the 1970s and 1980s. The emphasis is on the politics of memory in the Macedonian society actual during the Yugoslavian period as well as after the breakup of Yugoslavia, concerning the politics of representation and commemoration of the year 1878 and two crucial political events for the Macedonian question: the Treaty of San Stefano and the Congress of Berlin. The main hypothesis of the paper is that the play Flying in place is a historical drama and drama about history in which some traumatic spots from the Macedonian history are actualized.
Keywords: Goran Stefanovski, Macedonian drama, politics, collective memory, history